1982
DOI: 10.3109/00016488209130871
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Separation and Identification of Perilymph Proteins in Cases of Acoustic Neuroma

Abstract: Previous studies of perilymph proteins have emphasised the difficulty of obtaining samples free of blood or serum proteins. The present investigation has established a method of polyacrylamide gel electrophoresis, which enables contaminated specimens to be readily identified and therefore discarded. Analysis of uncontaminated samples has confirmed the presence of an elevated perilymph protein in cases of acoustic neurinomata. Perilymph proteins have been separated and identified and although no characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Previous studies indicate that the presence of a VS causes significant biochemical alterations of the inner ear fluids (31Y33), with an increased perilymphatic protein content (33,34). It has been suggested that these alterations are related to vascular impairment caused by mechanical obstruction by the VS (30,31). This hypothesis may be supported by Lapsiwala et al (35), who found a significant correlation between IAC pressure and preoperative hearing level.…”
Section: Predictors Of Change In Audiologic Functionmentioning
confidence: 84%
“…Previous studies indicate that the presence of a VS causes significant biochemical alterations of the inner ear fluids (31Y33), with an increased perilymphatic protein content (33,34). It has been suggested that these alterations are related to vascular impairment caused by mechanical obstruction by the VS (30,31). This hypothesis may be supported by Lapsiwala et al (35), who found a significant correlation between IAC pressure and preoperative hearing level.…”
Section: Predictors Of Change In Audiologic Functionmentioning
confidence: 84%
“…2,7,8 These studies have not found a relationship between perilymph protein levels and the degree of hearing loss or abnormalities of eighth nerve action potentials. Given the likelihood of contamination of perilymph with blood and other fluids during the surgical procedure and the small quantities of the fluid obtained during the procedure, these rela- tionships have not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…4 The pathogenesis of increased inner ear perilymph protein has been a matter of considerable investigation in the past. 4,[6][7][8][9] However, to date, no one agrees on a satisfactory explanation for this phenomenon. Furthermore, it has also remained unclear if protein levels in perilymph correlate with the degree of hearing loss and abnormal eighth nerve action potentials in patients with vestibular schwannoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,[10][11][12] The most plausible mechanisms include blockage of the neuroaxonal transport of proteins caused by compression of the vestibulocochlear nerve, cochlear membrane damage caused by arterial stasis and a consequent increased permeability, and a cell-mediated immune reaction to the inner ear caused by the antigenic properties of AN. [7][8][9][10][11][12]23 Among the 3 hypotheses, protein blockage from compression of the corresponding nerve is considered to be the dominant mechanism, with the others being minor in their contribution. Given that the cochlear signal reflecting the protein concentration correlates well with the degree of hearing loss represented by PTA in AN IAC but not in AN CPA , we could hypothesize that the degree of nerve compression is a major contribution to increasing the protein concentration while the tumor is confined to the internal auditory canal.…”
Section: Discussionmentioning
confidence: 99%